1999
DOI: 10.1136/jcp.52.10.787
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of women with borderline cervical smears as defined by national guidelines

Abstract: Aim-To determine the proportion of women with abnormalities in cervical smears corresponding to borderline nuclear change, as defined by national guidelines, which return to normal or persist as cytological or histological abnormalities. Methods-313 women with borderline nuclear change diagnosed by a single pathologist using the national criteria were followed up for up to two years. Results-On initial follow up, 45% of women had a negative smear or biopsy, 46.5% had a low grade cytological or histological abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…BNCH was an uncommon primary diagnosis in this laboratory (0.096% of all cervical smears) which yielded a 35% rate of high‐grade disease (CIN2 or worse) on clinicopathological follow‐up. This contrasts with follow‐up rates of high‐grade disease for BNC NOS and ASCUS NOS of 9.0–16.8% 10,13,16–18 . It is also greater than the 26.7–27.6% high‐grade rate on follow‐up of CIN1 or HPV‐positive ASCUS 19 .…”
Section: Discussionmentioning
confidence: 64%
“…BNCH was an uncommon primary diagnosis in this laboratory (0.096% of all cervical smears) which yielded a 35% rate of high‐grade disease (CIN2 or worse) on clinicopathological follow‐up. This contrasts with follow‐up rates of high‐grade disease for BNC NOS and ASCUS NOS of 9.0–16.8% 10,13,16–18 . It is also greater than the 26.7–27.6% high‐grade rate on follow‐up of CIN1 or HPV‐positive ASCUS 19 .…”
Section: Discussionmentioning
confidence: 64%
“…A more restricted sampling of the cervix may be possible in patients with negative smears or biopsies between initial treatment and diagnosis and the eventual hysterectomy because none of the 16 cases studied had residual disease, although a recent study indicates that even patients with borderline nuclear changes on initial smear may be found to have high grade CIN lesions despite interim negative smears. 11 Even in this situation, it is probably wise to examine more than the usual midline blocks taken in "routine" hysterectomy specimens, because none of the 27 patients whose hysterectomy cervix was sampled in two such blocks showed a CIN lesion, despite two having had high grade lesions diagnosed shortly before the hysterectomy. 12 13 The results support the continued practice of examining the entire cervix in hysterectomy specimens in women with a previous cervical abnormality, regardless of its histological or cytological grade, in the presence of interim positive smears or biopsies, or if such surveillance is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1986, it has been well recognized that borderline cytology could include cases of cervical intraepithelial neoplasia grade 2+ (CIN2+), thus requiring investigation 2,4 . The borderline nuclear change cytological category has been associated with 10–20% of CIN2+, which includes CIN2, CIN3, cervical glandular intraepithelial neoplasia (CGIN) and cancer 2,5–8 . The category B/HG attempts to refine further the borderline category, to triage for earlier colposcopy referral and to improve the negative predictive value (NPV) of borderline cytology and the positive predictive value (PPV) of high‐grade cytology.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the PPV of B/HG cytology (as of ASC‐H) for predicting CIN2+ has been shown to range between 19 and 59%, 3,7–9 compared with a PPV of 65–90% for high‐grade cytology 5,6,10 . It has been shown that features such as degenerate small metaplastic cells with high nuclear cytoplasmic ratios and the presence of hyperchromatic crowded cell groups 1 increase the PPV of borderline cytology 7,8 in both liquid‐based cytology (LBC) specimens and conventional smears, and that, equally, these can be the cause of false negative reports if not interpreted correctly. Prior to LBC and the introduction of the B/HG category, it has been the practice of cytologists in our department to report cervical cytology with atypical small cells or hyperchromatic crowded groups as moderate dyskaryosis (with subsequent lowering of the PPV for high‐grade dyskaryosis), or as borderline with the request for a repeat test.…”
Section: Introductionmentioning
confidence: 99%